Internet Surfing and Television Viewing Habits among Senior Secondary School Students in Ikorodu, Lagos Nigeria - Akin-Odukoya, Omolara Oluwabusayo; Owens-Ibie, Nosa (BIRCU, 2025)
This study investigates the internet surfing and television viewing habits of senior secondary school students in Ikorodu, Lagos, Nigeria. It aims to identify patterns, preferred content, time spent, and the impact on academic performance, social interactions, and lifestyle. Survey method was adopted to generate data and Cultivation Theory was employed in the study to address the subject under investigation. While these platforms provide valuable learning and entertainment opportunities, balanced use is crucial to mitigate potential negative effects on academic performance and health. The study revealed that students are fairly exposed to the usage of internet and television for information seeking usefulness contributes significantly to the relationship between students' involvement with salient issues as news and use of surfing as a relevant source as students were mostly motivated to read from the internet and television as part of daily news consumption. The patterns of internet surfing and television viewing habits vary significantly across different demographics, reflecting the influence of age, socioeconomic status, technological advancements, and cultural preferences. The findings highlight the influence of digital and television media on this demographic and provide recommendations for balanced media consumption. This study highlights the significant role of internet and television media in the lives of senior secondary school students. The habits surrounding internet surfing and television viewing reflect the growing integration of technology and media in daily life. While these platforms offer opportunities for learning, connectivity, and entertainment, it is essential to adopt strategies that mitigate their potential drawbacks. A collaborative approach involving individuals, families, educators, and policymakers can foster a balanced and healthy media consumption culture.